Inhibitory activity of thymol on native and mature Gardnerella vaginalis biofilms: in vitro study - Braga, Pier Carlo; Sasso, Monica Dal; Culici, Maria; Spallino, Alessandra (Arzneimittelforschung, 2010)
Bacterial vaginosis (BV) is the most frequent diagnosis made in women with lower genital tract symptoms. It has recently been observed that 90% of subjects with BV show the growth of bacteria in the form of biofilms as against only 10% without BV, and that Gardnerella vaginalis was the predominant species. The propensity of G. vaginalis to form biofilm is clinically relevant because this form of growth allows it to tolerate higher concentrations of certain antibiotics, thus increasing the possibilty of recurrent BV even after apparently curative therapy. The aim of this study was to investigate whether thymol (CAS 89-83-8), a molecule present in thyme essential oil, that is credited with having a series of pharmacological properties including antimicrobial and antifungal effects, can interfere with newly formed and mature G. vaginalis biofilms. The ability of G. vaginalis ATCC 49145 and two G. vaginalis strains isolated from human BV to form biofilm in flat-bottomed 96-well microtitre plates was verified, and the effects of thymol concentrations ranging from 1 to 1/16 MIC (minimum inhibitory concentration) on preformed and mature biofilms was investigated by means of spectrophotometric analysis, Nomarski interference contrast microscopy, and fluorescence microscopy with live-dead cell visualisation (SYTO 9 and propidium iodide). Native biofilm was inhibited by concentrations ranging from 1 MIC to 1/8 MIC (32.77% ± 2.37 to 11.39% ± 1.46), and mature biofilm was inhibited by concentrations ranging from 1 MIC to 1/4 MIC (26.18% ± 1.36 to 13.20% ± 1.44). Nomarski interference contrast and fluorescence microscopy visually confirmed these findings. As biofilm is a multi-factorial phenomenon, the multiple mechanisms of thymol may act on different steps in the evolution of mature biofilm.
Keywords: Antimicrobials; CAS 89-83-8; Fluorescence microscopy; Gardnerella vaginalis; Mature biofilm; Native biofilm